PERAN KEPEMIMPINAN TRANSFORMASIONAL DALAM MEMBANGUN BUDAYA ORGANISASI YANG INOVATIF - Nurhidayatullah; M. Sidiq Purnomo (CV. ADIBA AISHA AMIRA, 2024)
AbstractDarul Huda Lebak Kajang Islamic Boarding School, East OKU. Through a qualitative approach and case study methods, including participant observation, in-depth interviews, and document analysis, this research found that transformational leadership is effective in creating an environment that supports innovation and optimal growth in spiritual, intellectual, and social aspects. The transformational leader at this Islamic boarding school sets a clear vision, involves all members of the community, and encourages continuous learning and acceptance of new ideas. An innovative organizational culture in Islamic boarding schools is created through increasing organizational effectiveness, forming a strong identity, and empowering collaboration and creativity among students. The Islamic boarding school's strong identity in religious values ​​and humanity-oriented teaching is the foundation for a continuous enthusiasm for learning. These findings emphasize the importance of transformational leadership in preparing Islamic boarding schools to face the dynamics of modern education and ensuring long-term success.